Bilateral incisional post laparoscopic hernia. Clinical case and literature review - Rondón-Tapia, Marta (2018)
The increased use of laparoscopy has resulted in additional complications specific to this type of approach, such as incisional hernias that are usually associated with trocar size larger than 10 millimeters. These are a rare complication of laparoscopic surgery, with a reported incidence below 1%. They are a cause of postoperative morbidity and require immediate surgery. All entry sites should be closed to avoid such complications. A case of bilateral post-laparoscopic incisional hernia is described. A 35-year-old female patient with a history of laparoscopic surgery with a 3-port approach presented with vomiting, moderate-intensity abdominal pain and abdominal distension. Computed axial tomography showed intestinal loops at the site of trocar placement in both iliac fossae. During emergency laparoscopy, distended bowel loops were found, with two portions included in the bilateral defects of the lower abdomen fascia.